Disguising Superman: How Glasses Affect Unfamiliar Face Matching. Issue 6 (21st August 2016) - Kramer, Robin S. S.; Ritchie, Kay L.
Summary: Could a simple pair of glasses really fool us into thinking Superman and Clark Kent are two different people? Here, we investigated the perception of identity from face images with a task that relies on visual comparison rather than memory. Participants were presented with two images simultaneously and were asked whether the images depicted the same person or two different people. The image pairs showed neither image with glasses, both images with glasses, and 'mixed' pairs of one image with and one without glasses. Participants' accuracies, measured by both percentage correct and d′ sensitivity, were significantly lower for 'mixed' trials. Analysis of response bias showed that when only one face wore glasses, people tended to respond 'different'. We demonstrate that glasses affect face matching ability using unconstrained images, and this has implications for both disguise research and authenticating identity in the real world. Copyright © 2016 John Wiley & Sons, Ltd.